Development and damping properties of a seismic linear motion damper with MR fluid porous composite rotary brake. (8th October 2020) - Nakano, Masami; Yang, Jian; Sun, Shuaishuai; Totsuka, Atsushi; Fukukita, Akira
Abstract: The particle sedimentation of the dispersed particles in magnetorheological (MR) fluids when off-working has been a challenging problem, causing adverse effect to their practical applications. In order to solve this problem, 'MR fluid porous composite' made of porous materials impregnated with MR fluid has been fabricated in this work. Its effect to prevent the particle sedimentation has been proved through contrast experiment. Its MR effect has also been measured and verified using a hand-made oscillatory rheometer. Utilizing the MR fluid porous composite, a small-scale seismic linear MR damper has been developed. The unique design of this seismic linear MR damper has enabled it to convert the linear motion (damping force) of the MR damper to the rotations (braking torque) of the MR brake with almost no transmission loss. The damping properties of the developed small-scale seismic MR damper were investigated experimentally to be found that the design target with the damping force to be 20 kN has been achieved when applying an electric current of 0.5 A. Then a theoretical model was derived to estimate the damping force. The simulation results demonstrate that the proposed model is good at describing the properties of the seismic linear MR damper.